2007
DOI: 10.1111/j.1464-5491.2007.02128.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial examining combinations of repaglinide, metformin and NPH insulin

Abstract: The approach using repaglinide, metformin and NPH insulin improved glycaemic control with a similar safety profile to conventional insulin initiation in T2DM and produced final glycaemic control similar to metformin and a twice daily biphasic insulin mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…In contrast to our findings, Duran et al showed statistically significant decrease in HbA 1c levels due to administration of repaglinide against acarbose concomitant consumption with glargine insulin (11). In contrast of our study, episodes of hypoglycemia were not reduced in Davies et al trial which was handled by insulin use through repaglinide and metformin administration (12). Totally, albumin excretion rates were slightly diminished and changes were dependent on the administration route of drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Duran et al showed statistically significant decrease in HbA 1c levels due to administration of repaglinide against acarbose concomitant consumption with glargine insulin (11). In contrast of our study, episodes of hypoglycemia were not reduced in Davies et al trial which was handled by insulin use through repaglinide and metformin administration (12). Totally, albumin excretion rates were slightly diminished and changes were dependent on the administration route of drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…Moderate grade evidence showed a modestly lower risk of hypoglycemia when metformin was combined with basal insulin or glargine, rather than a premixed insulin such as lispro 75/25 or aspart 70/30 (but not lispro 50/50), which was associated with an increased risk of mild-to-moderate hypoglycemia compared with metformin. [133][134][135][136][137][138] Comparative Effects of Combination Therapies on Other Adverse Events Among several RCTs, no adverse events related to the liver were noted for treatment with various drug combinations including metformin combined with sulfonylureas or thiazolidinediones, or the thiazolidinediones combined with sulfonylureas. 70,109,110 The RECORD study found that patients taking rosiglitazone in combination with either a sulfonylurea or metformin had double the risk of CHF compared with patients receiving a combination of sulfonylurea and metformin.…”
Section: Comparative Effects Of Combination Therapies On Hypoglycemiamentioning
confidence: 99%
“…Davies et al9 defined it as an episode occurring between evening injection and breakfast. Diamant et al10 defined it as an episode between bedtime and breakfast.…”
Section: Resultsmentioning
confidence: 99%